Review and analysis of existing methods to assess the Indoor Environmental Quality (IEQ) for office buildings - Cláudia de Castro Jacinto; Adilson Campos de Paula Junior; Sandra Maria Gomes Monteiro Silva; Ricardo Filipe Mesquita Silva Mateus (Acta Polytechnica CTU Proceedings)
Population in developed countries spend most of their time indoors, whether in their homes, workplaces, stores or leisure areas. Due to the COVID-19 pandemic, this situation worsened and now, more than ever, the importance of a high Indoor Environmental Quality (IEQ) is highlighted. The IEQ is very important in building performance since it is directly related to its occupants’ comfort, health, wellbeing, and productivity and the Sick Building Syndrome (SBS) concept. Therefore, it is essential to develop tools to support designers’ decision-making in the materialization of indoor environments with higher quality. From the state-of-art analysis, it is possible to conclude that the methods to assess the overall building performance already consider the IEQ. Still, most use an approach that does not cover all relevant indicators. In this context, this paper presents the first milestone of a research work that aims to develop a new method to rate the overall IEQ of office buildings in Portugal. The main objective of the present study is to propose a list of IEQ indicators for office buildings, adapted to the Portuguese context, based on the analysis of existing rating methods for buildings and the recommendations of national and international standards.